(untitled) (Journal of the College of Basic Education, 2022)
The best is what makes a chest for every word; Praise be to God for His grace; and thanks for his grace,And I congratulate his prayers and perpetuate them upon Amin and his revelation; advising his nation; Mohammed; And for those involved in what carriedHis family and companions.. as for after The language has been introduced to human thought as a general system that individuals share in followingIt is not something made by a particular individual or individuals; But it goes back to naturethe meeting; and emanates from collective life; And what this life spends expressing thoughts,And the exchange of ideas, and each individual is shrouded in a linguistic system that he receives from his community through learning and simulation. And it hurtshis voices in his moulds; He follows him in his understanding and expression. And he who prowls in the folds of the advanced knows with certainty that language is subject to standardsSociety, its customs, traditions and cultures. It is an inherent way to reveal the customs and level of societyurban;